Knowledge and Attitude of University Students in Kirkuk City Toward Premarital Screening Program, Kirkuk-Iraq - Miohammed A. Kadir; Sabah Haseeb Hasan; Ayhan Abdulqadir Haseeb (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The aim of study is to know the knowledge and attitude of Kirkuk university students towards premarital screening program. A cross sectional study was conducted on University students in Kirkuk, from April 2024 to March 2025. The number of females was higher than males. The questionnaire were focusing student demographic characteristics of gender, age, residency, occupation of father, family income, parent knowledge and attitude of the university students in Kirkuk towards premarital screening. A questionnaire form was used for data collection. Statistical analysis was used to analyze the data. A total of 814 university students out of 2000 completed the questionnaire form; the majority of students were 17-26 years old with mean age 22 years. In term of knowledge of students, 570(70%) had knowledge on premarital screening and 244(30%) had no knowledge about premarital screening. Statistically there were significant association between positive knowledge of students and residency, genetic diseases, family history (P<0.05) m but no significant association with age, father occupation, family income and consanguinity.